Sparkle Through Speech: My Courageous Voice & Growth Mindset 2.0 / Marni Jamil, Nur Afiqah Ab. Latif and Noraziah Mohd Amin - Jamil, Marni; Ab. Latif, Nur Afiqah; Mohd Amin, Noraziah (Academy of Language Studies, 2024)
The Academy of Language Studies (APB), Universiti Teknologi MARA, Penang Branch, orchestrated the "Sparkle Through Speech: My Courageous Voice & Growth Mindset 2.0" program on 27th December 2023, held at the Tun Abdul Razak Library (PTAR), UiTMCPP. Commencing at 8:30 a.m. and concluding at 12:00 p.m., the program aimed to afford primary school students the opportunity to proficiently acquire English language skills, thereby fostering the development of their talents, competencies, and self-assurance in consonance with the imperatives of the globalisation era. Moreover, the initiative sought to enhance the English language proficiency of primary school students, while concurrently nurturing their interest and self-confidence, specifically targeting the offspring of UiTM Penang Branch personnel. Thirty-five students, aged between 6 and 12 years, actively participated in the program. Employing an instructional methodology centred on the application of enjoyable learning practices, the program aspired to create an environment conducive to effective learning and teaching.